HIV risk and prevention among men who have sex with men in rural South Africa. Issue 1 (2nd January 2017) - Maleke, Kabelo; Makhakhe, Nosipho; Peters, Remco PH; Jobson, Geoffrey; De Swardt, Glenn; Daniels, Joseph; Lane, Timothy; McIntyre, James A; Imrie, John; Struthers, Helen
Abstract : Rural South African men who have sex with men (MSM) are likely to be underserved in terms of access to relevant healthcare and HIV prevention services. While research in urban and peri-urban MSM populations has identified a range of factors affecting HIV risk in South African MSM, very little research is available that examines HIV risk and prevention in rural MSM populations. This exploratory study begins to address this lack by assessing perceptions of HIV risk among MSM in rural Limpopo province. Using thematic analysis of interview and discussion data, two overarching global themes that encapsulated participants' understandings of HIV risk and the HIV risk environment in their communities were developed. In the first theme, "community experience and the rural social environment", factors affecting HIV risk within the broad risk environment were discussed. These included perceptions of traditional value systems and communities as homophobic; jealousy and competition between MSM; and the role of social media as a means of meeting other MSM. The second global theme, "HIV/AIDS knowledge, risk and experience", focused on factors more immediately affecting HIV transmission risk. These included: high levels of knowledge of heterosexual HIV risk, but limited knowledge of MSM-specific risk; inconsistent condom and lubricant use; difficulties in negotiating condom and lubricant use due to uneven power dynamics in relationships; competition for sexual partners; multiple concurrent sexual partnerships; and transactional sex. These exploratory results suggest that rural South African MSM, like their urban and peri-urban counterparts, are at high risk of contracting HIV, and that there is a need for more in-depth research into the interactions between the rural context and the specific HIV risk knowledge and behaviours that affect HIV risk in this population.